Single-Atom (Iron-Based) Catalysts: Synthesis and Applications - Singh, Baljeet; Gawande, Manoj B; Kute, Arun D; Varma, Rajender S; Fornasiero, Paolo; McNeice, Peter; Jagadeesh, Rajenahally V; Beller, Matthias; Zbořil, Radek (Chemical reviews, 2021)
Supported single-metal atom catalysts (SACs) are constituted of isolated active metal centers, which are heterogenized on inert supports such as graphene, porous carbon, and metal oxides. Their thermal stability, electronic properties, and catalytic activities can be controlled via interactions between the single-metal atom center and neighboring heteroatoms such as nitrogen, oxygen, and sulfur. Due to the atomic dispersion of the active catalytic centers, the amount of metal required for catalysis can be decreased, thus offering new possibilities to control the selectivity of a given transformation as well as to improve catalyst turnover frequencies and turnover numbers. This review aims to comprehensively summarize the synthesis of Fe-SACs with a focus on anchoring single atoms (SA) on carbon/graphene supports. The characterization of these advanced materials using various spectroscopic techniques and their applications in diverse research areas are described. When applicable, mechanistic investigations conducted to understand the specific behavior of Fe-SACs-based catalysts are highlighted, including the use of theoretical models.
Keywords: železo; Carbon; Catalysis; uhlík; Iron; Nitrogen; dusík; kovy; Metals; katalýza